2015
DOI: 10.1021/acs.jpcc.5b02767
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Black Titania Nanofibers: Influence of Hydrogen Plasma-Induced Disorder on the Electronic Structure and Photoelectrochemical Performance

Abstract: This work encompasses a facile method for tailoring surface defects in electrospun TiO2 nanofibers by employing hydrogen plasma treatments. This amiable processing method was proven with SQUID, EPR, and XPS to be highly effective in generating oxygen vacancies, accompanied by the reduction of Ti4+ centers to Ti3+, resulting in the formation of black titania. The treatment temperature was found to affect the Ti3+/Ti4+ ratios and surface valence, while preserving the original 1D morphology of the titania fibers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 39 publications
2
39
0
Order By: Relevance
“…A broad and remarkable EPR resonance at low‐field with a “ g ” factor of 2.097 was observed (Figure A), which was attributed to the active oxygen species sitting on the O vac . However, the asymmetric resonance, peculiarly at a higher field, implies the presence of Ti 3+ ( g ≈1.97) or Ti cations with a lower valence state, which is caused by the hydrogenation treatment and is essential to maintain the neutral charge of the deficient NHTA . However, only a small amount of Ti 3+ species was identified by X‐ray photoelectron spectroscopy (XPS), indicating that Ti 3+ mainly exist in the bulk because the Ti 3+ species are not stable on the surface and easily oxidized in air .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A broad and remarkable EPR resonance at low‐field with a “ g ” factor of 2.097 was observed (Figure A), which was attributed to the active oxygen species sitting on the O vac . However, the asymmetric resonance, peculiarly at a higher field, implies the presence of Ti 3+ ( g ≈1.97) or Ti cations with a lower valence state, which is caused by the hydrogenation treatment and is essential to maintain the neutral charge of the deficient NHTA . However, only a small amount of Ti 3+ species was identified by X‐ray photoelectron spectroscopy (XPS), indicating that Ti 3+ mainly exist in the bulk because the Ti 3+ species are not stable on the surface and easily oxidized in air .…”
Section: Resultsmentioning
confidence: 99%
“…[17,35] However,t he asymmetric resonance, peculiarly at ah igher field, implies the presence of Ti 3 + (g % 1.97) or Ti cationswithal ower valence state, which is caused by the hydrogenation treatment andi se ssential to maintain the neutral chargeo ft he deficientN HTA. [36] However, only as mall amount of Ti 3 + species was identified by X-ray photoelectron spectroscopy (XPS), indicating that Ti 3 + mainly exist in the bulk because the Ti 3 + speciesa re not stable on the surfacea nd easily oxidized in air. [34] The above analysis indicates that the Ti 3 + exists in the bulk of NHTAa nd O vac dominate the disordered NHTAsurface.…”
Section: Resultsmentioning
confidence: 99%
“…[ 71 ] Additionally, black anatase TiO 2 nanoparticles, [ 72 ] blue (111)facet exposed TiO 2 nanosheets with Exposed (001), [ 73,74 ] hydrogenate TiO 2 fi lm [ 75 ] and black TiO 2 nanofi ber [ 76 ] were also successfully obtained by H 2 plasma treatment. [ 71 ] Additionally, black anatase TiO 2 nanoparticles, [ 72 ] blue (111)facet exposed TiO 2 nanosheets with Exposed (001), [ 73,74 ] hydrogenate TiO 2 fi lm [ 75 ] and black TiO 2 nanofi ber [ 76 ] were also successfully obtained by H 2 plasma treatment.…”
Section: Wileyonlinelibrarycommentioning
confidence: 96%
“…[ 70 ] First-principle calculations by Lu et al suggested that the H adatoms induced mid-gap states located close to the VBM for the (101) and (100) surfaces of anatase phase TiO 2 . [ 128,129 ] With the increase of oxygen vacancy/Ti 3+ concentration, the Ti 3d band shifts deeper and exhibits multiple bands with a width of 0.5−1.5 eV below the CB minimum, [ 16,27,39,48,62,76,109,130 ] as shown in Figure 28 a−e. [ 126 ] However, Sotoudeh suggested that H-doping in the oxygen defective TiO 2x system could remove the O-vacancy mid-gap and created an empty mid-gap state below the conduction band.…”
Section: Electronic Structure Of Black Titaniamentioning
confidence: 99%
“…Hydrogen plasma technology has attracted increasing interest owing to its effectiveness in engineering surface-disordered TiO 2 nanomaterials with a typical crystalline/amorphous core/shell structure [33,39,57,60]. Ti 3+ species and oxygen vacancies were reported to be the primary defects in some cases [57,58], while Ti-H groups and oxygen vacancies were believed to be the dominant defects in other cases [33,39].…”
Section: Black Tio 2 Nanomaterials As Visible Light-active Photocatalmentioning
confidence: 99%